2021
DOI: 10.1007/s13555-021-00556-2
|View full text |Cite
|
Sign up to set email alerts
|

Risankizumab for the Treatment of Moderate-to-Severe Psoriasis: Real-Life Multicenter Experience from the Czech Republic

Abstract: Introduction: Risankizumab has been approved for the treatment of moderate-to-severe plaque psoriasis; however, real-life data are limited. Our objectives were to evaluate the effectiveness and safety of risankizumab and its impact on the quality of life of patients with psoriasis in a realworld setting. Methods: We retrospectively analyzed 154 patients from 18 centers in the Czech Republic who had undergone biologic therapy with risankizumab for moderate-to-severe plaque psoriasis. Baseline characteristics in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
52
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(74 citation statements)
references
References 20 publications
17
52
5
Order By: Relevance
“…To date, there is no study dedicated to risankizumab in PsA patients. Although in phase III and real‐life studies the affected population also at the joint level is between 20–30%, no specific efficacy analysis has been performed on this subpopulation 2–4 . In our study, 22% of patients had joint involvement, which is in line with the current literature, and showed a generally poorer response to treatment.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…To date, there is no study dedicated to risankizumab in PsA patients. Although in phase III and real‐life studies the affected population also at the joint level is between 20–30%, no specific efficacy analysis has been performed on this subpopulation 2–4 . In our study, 22% of patients had joint involvement, which is in line with the current literature, and showed a generally poorer response to treatment.…”
Section: Discussionsupporting
confidence: 89%
“…The reduction of the mean PASI in our population was consistent as early as 16 weeks and showed a tendency for further reduction at subsequent endpoints. The mean PASI score decreased from 12.5 (SD 5.1) at baseline to 1.9 (SD 2.4) at week 16 which is similar to the mean PASI score reported in the Czech study by Gkalpakiotis et al on 94 patients and an Italian study by Megna et al on 8 patients, 1.7 (SD 2.3) and 3.3 (SD 1.7), respectively 2,10 . We observed a similar reduction in the achievement of PASI 100, PASI 90, PASI 75, and PASI <3.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Robust and durable responses with risankizumab have also been demonstrated outside the clinical trial setting. A retrospective analysis of 154 patients with moderate-to-severe plaque psoriasis from multiple centers in the Czech Republic who were treated with risankizumab and followed up to 1 year found that PASI90 and PASI100 were achieved by 63.8% and 44.7% of patients, respectively, at week 16 and 82.4% and 67.6% of patients, respectively, at week 52 [ 19 ]. This trend was accompanied by an improvement in life quality, as reflected by a decline in DLQI over time.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the levels of IL-17A, IL-22, and IL-23 were significantly enhanced in patients with active disease compared with those with stable diseases (39). Olejniczak-Staruch et al and Gkalpakiotis et al documented that long-term biologic therapy with anti-TNFα drugs improved the PASI score, reduced systemic and local inflammation, and decreased the markers of inflammation such as CRP, IL-2, IL-22, etc (40,41). Correlation between IL-22 and severity of disease and between IL-22 and IL-17 was proven in studies by Sobhan et al and Elala et al Sobhan discovered that the level of IL-22 was significantly higher in patients with psoriasis compared to healthy controls and correlated with PASI (42,43).…”
Section: Discussionmentioning
confidence: 99%